2021
DOI: 10.1101/2021.08.12.456131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic reconciliation reveals extensive ancestral recombination in Sarbecoviruses and the SARS-CoV-2 lineage

Abstract: An accurate understanding of the evolutionary history of rapidly-evolving viruses like SARS-CoV-2, responsible for the COVID-19 pandemic, is crucial to tracking and preventing the spread of emerging pathogens. However, viruses undergo frequent recombination, which makes it difficult to trace their evolutionary history using traditional phylogenetic methods. Here, we present a phylogenetic workflow, virDTL, for analyzing viral evolution in the presence of recombination. Our approach leverages reconciliation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…There is both in silico [51] and in vivo [52] evidence for recombination of different SARS-CoV-2 strains. Studies relying on linkage disequilibrium identified that SARS-CoV-2 recombination occurs at very low levels [52][53][54] or does not occur at all [55][56][57][58][59][60]. Several alternative methods are available for reconstructing genealogies explicitly in the presence of recombination, both with [61] and without [62][63][64] making the parsimony assumption, but none is tailored to the particular problem of detecting recombination in the presence of recurrent mutation.…”
Section: Evidence For Recombination In Sars-cov-2mentioning
confidence: 99%
“…There is both in silico [51] and in vivo [52] evidence for recombination of different SARS-CoV-2 strains. Studies relying on linkage disequilibrium identified that SARS-CoV-2 recombination occurs at very low levels [52][53][54] or does not occur at all [55][56][57][58][59][60]. Several alternative methods are available for reconstructing genealogies explicitly in the presence of recombination, both with [61] and without [62][63][64] making the parsimony assumption, but none is tailored to the particular problem of detecting recombination in the presence of recurrent mutation.…”
Section: Evidence For Recombination In Sars-cov-2mentioning
confidence: 99%
“…One opinion thinks that ACE2 binding represents an ancestral and evolvable trait of sarbecoviruses and evolutionary deletions in two specific regions of RBDs led to the loss of the property in the ACE2 non-utilizing SL-CoVs (Shi and Wang, 2011;Starr et al, 2022); the other opinion insists that natural genetic recombination with other evolutionarily related viruses created this property (Boni et al, 2020;Wells et al, 2021). For example, based on phylogenetic reconciliation, it is inferred that extensive ancestral recombination might have occurred in sarbecoviruses including the SARS-CoV-2 lineage (Zaman et al, 2021). Comparative genomic analysis suggests that SARS-CoV-2 may have originated in the recombination of a virus similar to pangolin-CoV with one similar to RaTG13 (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the authors' points of view are at opposite poles about the role of recombination in the evolution of SARS-CoV-2. Therefore, despite intensive studies worldwide (Hu et al, 2017;Cui et al, 2019;Boni et al, 2020;Xiao et al, 2020;Wells et al, 2021;Zaman et al, 2021), how these sarbecoviruses evolutionarily gained such ability especially in their early history is unresolved and certain to remain controversial, hindering a better understanding of their receptor shift to break through the species barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was expected that SARS-CoV-2 would evolve slowly due to the proofreading ability of its polymerase enzyme (8). Hence, earlier studies relying on linkage disequilibrium identified limited instances of viral recombination and evolution (9)(10)(11)(12)(13)(14). This has facilitated the emergence of divergent SARS-CoV-2 lineages worldwide, including Alpha, Beta, and Gamma variants of concern (VOCs).…”
Section: Introductionmentioning
confidence: 99%